The evidentiary basis of vertebral augmentation: a 2019 update. (22nd January 2020) - De Leacy, Reade; Chandra, Ronil V; Barr, John D; Brook, Allan; Cianfoni, Alessandro; Georgy, Bassem; Jhamb, Ashu; Lohle, Paul N M; Manfre, Luigi; Marcia, Stefano; Venmans, Alexander; Bageac, Devin; et al.
Abstract : No aspect of neurointerventional practice has been associated with as longstanding contention and debate as to its effectiveness as has vertebroplasty (VP). Four blinded randomized controlled trials published since 2009 have demonstrated conflicting results regarding a conferred benefit in pain reduction and functional improvement for patients who undergo VP for osteoporotic vertebral compression fractures. Significant heterogeneity exists between each of these trials, which has resulted in difficulty for interventionalists and surgeons to translate the trial findings into routine clinical practice. In addition, patients and their families are ever more enlightened and enabled via the internet and social media to review both medical literature and websites. Without the proper background and context, their decisions may be lacking appropriate and necessary scientific discussion. This review article summarizes the randomized controlled trial data to date, with particular focus on the aforementioned four blinded studies. We will also evaluate the profound impact of the decrease in vertebral augmentation utilization on short- and long-term patient morbidity and mortality using available national and administrative datasets from both within the USA and internationally. We also consider future trial design to help evaluate this procedure and determine its role in modern neurointerventional practice.